A practical strategy for individualized training monitoring : training load, cardiac autonomic function, jump height, and mood in young diving athletes - Bernardes Neto, Roque (2022)
Dissertação (Mestrado) — Universidade de Brasília, Faculdade de Educação Física, Programa de Pós-Graduação em Educação Física, 2022.